1993
DOI: 10.1007/bf00012859
|View full text |Cite
|
Sign up to set email alerts
|

Length densities, occupancies and weights of apple root systems

Abstract: The root systems of apple trees from five orchards ranging in age from 1.5-y to 14-y were sampled to depths of between one and two metres using soil cores. Although trees came from orchards which differed in soil-type, tree spacings and management, consistent patterns were found in root systems. In orchards of 4-y and older, roots of adjacent trees met so that soil volumes within the planting grids (i.e, tree spacings of approximately 5 m inter-row x 4 m intra-row distances) were completely explored, although … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

1995
1995
2021
2021

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 13 publications
1
16
0
Order By: Relevance
“…In most reports that consider root development, stumps and large roots are excavated in time series with individual trees showing remarkably consistent relationship between above and belowground biomass that varies little among taxa and environment (cf Enquist and Niklas 2002). In a smaller number of studies, rooting density has been used to monitor site occupation by forest tree root system (Adegbidi et al 2004;Bouillet et al 2002;Hughes and Gandar 1993;Luxrnoore et al 1993;Misra et al 1998;Narnbiar 1983;O'Grady et al 2005;Zutter et al 1999). As in our work (Figs.…”
Section: Aboveground Growthsupporting
confidence: 59%
See 1 more Smart Citation
“…In most reports that consider root development, stumps and large roots are excavated in time series with individual trees showing remarkably consistent relationship between above and belowground biomass that varies little among taxa and environment (cf Enquist and Niklas 2002). In a smaller number of studies, rooting density has been used to monitor site occupation by forest tree root system (Adegbidi et al 2004;Bouillet et al 2002;Hughes and Gandar 1993;Luxrnoore et al 1993;Misra et al 1998;Narnbiar 1983;O'Grady et al 2005;Zutter et al 1999). As in our work (Figs.…”
Section: Aboveground Growthsupporting
confidence: 59%
“…Temporal responses are equally important to define. For instance, root systems proliferate during forest stand establishment in proportion to plant production (Adegbidi et al 2004;Hughes and Gandar 1993;Misra et al 1998;O'Grady et al 2005), indicating increased root system capacity for nutrient and water acquisition. Defining spatial and temporal variation is essential to determining the relative magnitude of genetic and environmental fictors.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, extensive soil coring in mature apple and kiwifruit orchards has shown that mean RLDs do not vary with distance from tree stems. (Gandar and Hughes, 1988;Hughes and Gandar, 1993). This does not mean that tree roots do not intermingle by intruding into empty space outside their allocated area.…”
Section: Available Volumes and Standard Volumementioning
confidence: 99%
“…However Hughes and Gandar (1993) noted that apples appear to explore available soil volumes substantially faster than kiwifruit. Because our five sampled species have different mean ages (Table 3) it is possible that some of the differences between mean exploitation indices (Table 2) could be attributed to differences in rootstock age.…”
Section: Effects Of Plant Agementioning
confidence: 99%
See 1 more Smart Citation